Social network addiction and mental disorders in human medicine students at a Peruvian university. - Contreras-Tello, C.D. (2022)
Objectives: to determine the relationship between addiction to social networks and the presence of mental disorders in medical students at a university in Cajamarca in the year 2024. Method: the study had a quantitative approach, non-experimental, cross-sectional and correlational design. It involved the participation of 114 students, who filled out a survey consisting of two questionnaires: “Addiction to Social Networks” and Depression, Anxiety and Stress Abbreviated Scales (DASS-21), which are validated with Combrach’s alpha 0,95 and 0,933 respectively. Results: respondents are mostly aged 16-20 years and 54,4 % were female. A high prevalence level (98,2 %) of addiction to social networks was calculated; meanwhile, the prevalence of anxiety, depression and stress were 51,2 %, 46,5 % and 43 %, respectively. A significant association was found between depression and stress with respect to social network addiction (p=0,01 and p=0,02, respectively); however, no significant relationship was found between the anxiety dimension and social network addiction (p=0,158). On the other hand, there was a significant relationship between anxiety (p=0,003) and stress (p=0,02) with sex, as well as between anxiety (p=0,024) and depression (p=0,025) with academic grade. Conclusions: depression and stress were found to be related to social network addiction in medical students studying basic sciences.